Effectiveness of the physiotherapist's matrix support for community health agents: a quasi-experimental study. - Neves Barbosa, Samara Maria; Menezes Silva, Gabriel Brighenti; Silveira Costa, Henrique; de Carvalho Bastone, Alessandra; Fernandes de Melo Vitorino, Débora; Nunes Santos, Juliana (Fisioterapia em Movimento)
Introduction: Primary health care (PHC) represents the first step of a network of health care processes that have the Family Health Strategy as their foundation for reorganization, expansion and consolidation. Objective: To investigate the effectiveness of the matrix support provided by the physical therapist to the community health agents (CHAs) regarding the level of knowledge about health conditions responsive to the performance of physiotherapy in PHC. Methods: We conducted a quasi-experimental study with two groups of CHAs, divided into control (n = 6) and intervention (n = 7), totaling 13 professionals belonging to a small municipality. Matrix support took place through educational workshops, addressing the axes of maternal and child health, adult health, health of older people and musculoskeletal disorders. For the initial assessment, a semi-open questionnaire was administered with sociodemographic data and work-related questions, a structured questionnaire containing questions related to the performance of physiotherapy in PHC that presents situations from the CHA's work routine, and a semi-open survey investigating patients to be referred to physiotherapy. For the final assessment, the same instruments were reapplied, except for the sociodemographic questionnaire. Results: After the intervention, in the comparison between groups, there was a difference in the risk perception index in the axis of musculoskeletal disorders (p = 0.032) and in the identification of cases of childhood changes (p = 0.012). In the intragroup comparison, the intervention group showed a difference in risk perception in the health of the older persons and in most of the items of the referral survey (p < 0.05 for all). Conclusion: Matrix support can contribute to the shared construction of knowledge, as well as to the activation of physiotherapy in PHC by CHAs.